What is intellectual property and how do you protect it?. Issue 2 (February 2017) - Graves, Jamie
Abstract : Intellectual property (IP) theft is running rampant. Some organisations know it and disclose any loss of IP that occurs. Other organisations know it but keep their IP disclosures under wraps for as long as they can. The rest … well, they may be leaking IP at this very second and be none the wiser. Lack of information classification, information security policies and access control measures protecting IP can make for a very sticky situation. Almost every company has intellectual property of some sort, even if it doesn't know it. So how do you know if you have IP? And how can you protect it once you figure out what it is? Intellectual property (IP) theft is running rampant. Some organisations know it and disclose any loss of IP that occurs. Other organisations know it but keep their IP disclosures under wraps for as long as they can. Lack of information classification, information security policies and access control measures protecting IP can make for a very sticky situation. Almost every company has intellectual property of some sort, even if it doesn't know it. So how do you know if you have IP? And how can you protect it once you figure out what it is? Jamie Graves of ZoneFox looks at how you identify key IP in your organisation and develop a strategy to safeguard it.